Light in the beam dump: Axion-Like Particle production from decay photons in proton beam-dumps - Döbrich, Babette; Jaeckel, Joerg; Spadaro, Tommaso (Journal of high energy physics, 2019)
The exploration of long-lived particles in the MeV-GeV region is a formidable task but it may provide us a unique access to dark sectors. Fixed-target facilities with sufficiently energetic and intense proton beams are an ideal tool for this challenge. In this work we show that the production rate of Axion-Like-Particles (ALPs) coupled pre-dominantly to photons receives a significant contribution from daughter-photons of secondary π0 and η mesons created in the proton shower. We carefully compare the PYTHIA simulated spectra of such secondaries to experimental literature, compute the ALP flux from the Primakoff conversion of these photons, and finally revisit existing limits on ALPs and update the prospects for a set of existing and future searches. Our results show that taking this production mechanism into account significantly enhances the sensitivity compared to previous studies based on coherent ALP production in primary proton-nucleus interactions.